Internal Wave Transport, Nonlinear Manifestation, and Mixing in a Stratified Shear Layer - Technical Briefs - Chen-Yuan Chen (Prime Archives in Internal Waves, 2022)
Internal solitary waves (ISWs) have been detected at the interface of a stratified water column in the laboratory. This paper reports upon the propagation of an ISW in various pycnoclinees. The thickness of the pycnocline was estimated from the resulting density profile in the vertical direction. Based on the results obtained, the dimensionless thickness (=B/H, where B is pycnocline; H the total depth of 50 cm) of the first test was 0-0.1 in ISW. Our experimental results show that, as the thickness of the pycnoline increases, the values of all the physical parameters (e.g., wave amplitude, phase speed, and wave energy) decreases. The findings of this study should be beneficial to oceanography and advanced research regarding ISW propagation and the evolution of both laboratory experiments and in-situ measurements.